Determination of Dividend Policy in Indonesian Banking - Heriansyah, Kurnia; Permata, Irma Sari; Widayadi, Wasi (JACTA: Journal of Accounting and Tax, 2023)
The company's dividend policy must be formulated with two primary objectives, namely providing adequate financing and maximizing the wealth of the company's owners. Shareholders see dividends as a signal of future banking success, stable and sustainable dividends are a positive signal, and vice versa. This study aims to determine the effect of profitability, liquidity, capital adequacy, institutional ownership, and asset growth on dividend policy. This type of research uses explanatory research. The research sample consisted of 13 banks listed on the Indonesia Stock Exchange from 2015-2019. The results show that profitability has no effect on bank dividend policy, liquidity has an effect on bank dividend policy, capital adequacy has an effect on bank dividend policy, institutional ownership has no effect on bank dividend policy.